Evaluating the psychometric soundness of Bostick's library anxiety scale among medical students in a Malaysian public university - Karim, N.H.A.; Shamsuddin, N.N.A.N. (2014)

(untitled)
The study was about exploring the phenomenon of library anxiety among medical students and examines various antecedents that may contribute towards increasing or decreasing level of library anxiety. Bostick's (1992) Library Anxiety Scale has been widely used to assess library anxiety among library users. The instrument was pre-tested and the reliability and validity of the scale was established. The 46-item modified version of Bostick's (1992) Library Anxiety Scale was tested among 104 students from a population of 354 undergraduate students. The instruments were administered during information skills sessions by copies handed directly to students. A 100% return rate was achieved in which the questionnaires that were returned were found usable. The findings revealed a a-factor solution which corresponded to the five factors as found by Bostick's (1992) pioneering psychometric effort on library anxiety. The study sub-scales of library anxiety were named as: Staff Barriers, Affective Barriers, Barriers with Library Technology, and Cognitive Barriers. The factor "Staff Barriers" explained the greatest proportion of variance to be at 19.12% in the library anxiety construct. The overall scale as well as each of the four subscales was submitted to an internal reliability assessment using Cronbach's internal reliability coefficient alpha. All four sub-scales found to have satisfied the 0.70 criteria as recommended by Nunnally and Bernstein (1994). This finding was found to be consistent with the previous studies that found the scale to be valid as well as internally reliable.